TERMINOLOGY IN PROCESS MANAGEMENT - Igor G. Fedorov (Открытое образование (Москва))
We can be mistaken to formulate basic concepts of process management, and we are at risk to be on the wrong way solving the focused problems – instead of process management we could do automatization, instead of process system we could introduce function-oriented system. Without having a clear idea of the model we have to execute, we can plan this model as an analytical one and do not include all the necessary tools for management on the stage of planning. The article is targeted for the analysts who have skills in analytical modeling of business processes and would like to make a step forward to the implementation of these models. In order to become professionals in this field it is necessary to learn the terminology, first of all.